Efektivitas kombinasi pupuk kandang kambing dan POC Jakaba terhadap pertumbuhan dan hasil Pakcoy - Akmal Faturahman; Sulkifli; Andi Cakra Yusuf (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2026)
The decline in soil fertility due to the continuous use of inorganic fertilisers has impacted pakcoy productivity, necessitating organic alternatives. This study aims to determine the effectiveness of the combination, dosage, and ratio of Jakaba Liquid Organic Fertiliser (POC) and goat manure compost on the growth and yield of pakcoy (Brassica rapa L.). The research was conducted from May to July 2025 at the Green House of the Faculty of Agriculture and Animal Husbandry, Muhammadiyah University of Bone. The method used was a Factorial Completely Randomised Design (CRD) consisting of 12 treatment combinations of goat manure doses (0, 180, and 360 g plant⁻¹) and Jakaba POC concentrations (0, 60, 100, and 200 ml L⁻¹) with 6 replications, totalling 72 experimental units. Observation parameters included plant height, number of leaves, leaf area, fresh weight, consumption weight, and yield per hectare. The results showed that applying 180 g plant⁻¹ of goat manure and 60 ml L⁻¹ of Jakaba POC (K1J3) produced the highest fresh weight, consumption weight, and productivity (36.85 tons ha⁻¹). In conclusion, the combination of goat manure and Jakaba POC is effective in increasing pakchoi growth and production, serving as a viable organic cultivation technique.